Shape Memory Polymer Nanofibers and Their Composites: Electrospinning, Structure, Performance, and Applications - Zhang, Fenghua; Zhang, Zhichun; Zhou, Tianyang; Liu, Yanju; Leng, Jinsong (Frontiers in Materials, 2015)
Shape memory polymers (SMPs) have been defined as a kind of smart materials under great investigation from academic research to industry applications. Research on SMPs and their composites, now incorporates a growing focus on nanofibers which offers new structures in microscopic level and the potential of enhanced performance of SMPs. This paper presents a comprehensive review of the development of shape memory polymer nanofibers and their composites, including the introduction of electrospinning technology, the morphology and structures of nanofibers (non-woven fibers, oriented fibers, core/shell fibers and functional particles added in the fibers), shape memory performance (thermal and mechanical properties, stimulus responsive behavior, multiple and two-way shape changing performance), as well as their potential applications in the fields of biomedical and tissue engineering.